Reduction of enteric methane emission using methanotroph-based probiotics in Hanwoo steers - Tenzin Tseten; Rey Anthony Sanjorjo; Jong-Wook Son; Keun Sik Baik; Janine I. Berdos; Seon-Ho Kim; Sang-Hwal Yoon; Min-Kyoung Kang; Moonhyuk Kwon; Sang-Suk Lee; Seon-Won Kim (Animal Microbiome, 2025)
Abstract Background Methane emission from enteric rumen fermentation is a main source of greenhouse gas (GHG) emission and a major concern for global warming. Results In this study, we isolated methanotroph-methylotroph consortium NC52PC from the rumen after a series of sub-culture and repetitive streaking on an agar plate and polycarbonate membrane filter. The NC52PC comprises methanotroph species (Methylocystis sp.) and methylotroph species (Methylobacterium sp.), forming a consortium capable of growing solely on methane as a carbon source. Their morphology, growth, and genome sequence were characterized. We assessed its effectiveness in mitigating methane emissions through both in vitro and in vivo experiments. During the in vitro trial, the introduction of NC52PC (at a concentration of 5.1 × 107 CFUs/ml) demonstrated a reduction in methane production exceeding 40% and 50% after 12 and 24 h, respectively. Also, NC52PC did not significantly alter other aspects of the in vitro rumen fermentation parameters such as pH, total gas production, and digestibility. Further investigation involved testing NC52PC as a dietary supplement in 12 young Hanwoo steers over three 30-day test periods. The steers received a diet comprising 70.8% concentrate and 29.2% bluegrass on a dry matter basis, with variations including 3 × 107 CFUs/ml of NC52PC (LOW) and 3 × 108 CFUs/ml (HIGH) of NC52PC, and without NC52PC as a control (CON). Steers administered with HIGH and LOW concentrations of NC52PC exhibited reduced enteric methane emission (g/day) by 14.4% and 12.0%, respectively. Conclusion Feeding methanotroph-methylotroph consortium NC52PC significantly reduced methane emissions in Korean beef cattle without any adverse effects on animal health. These findings suggest that this probiotic could serve as a promising feed additive to effectively mitigate methane emissions from ruminants. However, further research is needed to evaluate the long-term effects of NC52PC on animal health, and on meat and milk quality.